The Learning Skills and Level of Understanding of Grade 9 Students on a Mathematics Lesson on Sequences and Series (European Journal of Pure and Applied Mathematics, 2025)
This study assesses the Algebra skills of Grade 9 students at IDS post-pandemic, using an open-ended mathematics questionnaire during the first week of the second quarter. It evaluates students' critical and creative thinking, and problem-solving abilities. Results show that while students have made progress in creative thinking and can generate original ideas, their understanding of Algebra remains at a basic level. Critical thinking and problem-solving skills are also at a benchmark level, indicating that students often replicate information without thorough analysis or questioning. To address these issues, the study recommends targeted remediation to enhance students' comprehension and skills in Algebra. It also suggests conducting a comparative qualitative study and exploring how different skill levels relate to overall understanding.
Keywords: Conceptual Understanding; Creative Thinking Skill; Problem Solving Skill; Reasoning Skills